Polypharmacy and potential drug–drug interactions for people with HIV in the UK from the Climate‐HIV database. Issue 8 (15th July 2020) - Okoli, C; Schwenk, A; Radford, M; Myland, M; Taylor, S; Darley, A; Barnes, J; Fox, A; Grimson, F; Reeves, I; Munshi, S; Croucher, A; et al.
Abstract : Objectives: People with HIV (PWHIV) are likely to need therapies for comorbidities as they age. We assessed risk of drug–drug interactions (DDIs) in PWHIV. Methods: The Climate‐HIV electronic recording system was used to cross‐sectionally analyse records from PWHIV aged ≥ 18 years attending four UK HIV units with a current antiretroviral (ARV) prescription in February 2018. Antiretroviral and non‐ARV medications were categorized by clinical significance of DDIs (University of Liverpool DDI tool). Potential DDIs were predicted using treatment guidelines for commonly recorded comorbidities. Results: Among 4630 PWHIV (44% female), 41% were ≥ 50 years old. The average number of non‐ARV comedications increased from < 1 for patients aged ≤ 24 years to > 5 for patients aged ≥ 75 years; 65% were taking one or more non‐ARV comedications. The median (interquartile range) number of non‐ARVs was 1 (0–2) and 2 (1–5) for those aged < 50 and ≥ 50 years, respectively. Common comorbidities/concurrent health conditions occurred more frequently in patients aged ≥ 50 years vs . < 50 (53% vs . 34%). Boosted protease inhibitors were associated with the highest proportion of contraindicated comedications; dolutegravir and raltegravir had the fewest. For non‐ARVs, sildenafil and quetiapine were most likely to result in DDIs. Guideline‐recommended treatments for hepatitis C, hepatitis B, and tuberculosis had the highest proportions of contraindications when combined with ARV regimens, while treatments for hepatitis C, malignancy, and mental health conditions had the highest proportion of combinations potentially causing DDIs requiring dose monitoring or adjustment. Conclusions: Non‐ARV use by PWHIV is high and increases with age. Treatment decisions for ageing PWHIV should consider guideline recommendations for comorbidities.